Konsep Akomodasi Wisata Halal di Propinsi NTB Berdasarkan Peraturan Daerah Nomor 2 Tahun 2016 Tentang Pariwisata Halal - Ady Supyadi; Hilman Syahrial Haq; Hamdi Hamdi (Universitas Muhammadiyah Mataram, 2018)
Islamic economy is instrumental to global economy to date. There are seven sectors of Islamic economy that has improved significantly, namely culinary, monetary, insurance industry, fashion, cosmetics, pharmacy, entertainment, and tourism, all of which bear halal concept in their products. This research study aimed to explore and analyze the description of tourist accommodation in Lombok before and after the issuance of West Nusa Tenggara Provincial Regulation Number 2 of 2016 on Halal Tourism and examine the efforts the government has made to materialize halal accommodation mandated by the regulation. This research is normative legal, i.e., legal research that analyzes rules or norms related to the issue being investigated. Data obtained from this research were analyzed using legal interpretation methods, including extensive interpretation and sociological or teleological interpretation. The findings revealed that before the issuance of Provincial Regulation Number 2 of 2016, the management of tourism in West Nusa Tenggara was conventional as opposed to sharia-based management upon the issuance of the regulation. In order to materialize halal accommodation the government has reviewed the master plan of tourism development and improved services and accommodation for domestic and international tourists.